Human papillomavirus genotypes and HPV-16 variants distribution among Tunisian women with normal cytology and squamous intraepithelial lesions. Issue 1 (December 2016) - Ghedira, R.; Mahfoudh, W.; Hadhri, S.; Gabbouj, S.; Bouanene, I.; Khairi, H.; Chaieb, A.; Khelifa, R.; Bouaouina, N.; Remadi, S.; Elmi, A.; Bansal, D.; et al.
Abstract Background Little is known about the epidemiological characteristics of papillomavirus (HPV) infection among North African countries. Herein, we conducted a molecular epidemiological study to investigate prevalence of HPV type and HPV-16 variants among cervical-screened unvaccinated Tunisian women. Methods Cross-sectional study was performed on 494 Tunisian women visiting Women's Healthcare Centers. HPV-DNA detection was carried out on cervical samples using real-time polymerase chain reaction. HPV genotyping and HPV-16 variants were characterized by direct sequencing ofL1 viral capsid gene. Results The overall HPV prevalence was 34% (95% CI: 30–38%) with significantly higher prevalence among women with squamous intraepithelial lesions (SIL) than those with no intraepithelial lesions (NIL) 84% (95% CI: 76–92%) and 24.5% (95% CI: 20–29%) respectively. The distribution of HPV prevalence according to women's age shows a U-shaped curve and the highest HPV prevalence rates were observed among the youngest (≤25 years; 51.2%, 95% CI: 37–67%) and the oldest women (>55 years; 41.7%, 95% The HPV-16 prevalence was 32.8% (95% CI: 22–45%) among women with SIL and 9.2% (95% CI: 6–12%) among women with NIL. Whereas, the HPV-18 prevalence was 1.3% (95% CI: 0–5%) among women with SIL and 0.3% (95% CI: 0–1%) among women with NIL. Among HPV-16 positive women, European lineage (E) was identified as the predominant HPV-16 variant (85.7%, 95% CI: 76–95%). The frequency of E variant was lower among SIL than among NIL women (81%, 95% CI: 64–99%, and 88%, 95% CI: 77–100%, respectively). Conversely, the African-2 variant frequency was higher among SIL than among NIL women (18%, 95% CI: 1–36% and 6%, 95% CI: 2–14%, respectively). In multivariate analysis, young age was the only risk factor that is independently associated with HPV infection. Moreover, HPV infection and menopause were both found to be independently associated with SIL and HSIL. Conclusion HPV DNA testing should be proposed to young and menopausal Tunisian women. Considering HPV prevalence, only 13% of the Tunisian women could be protected by the bivalent HPV vaccine. These results may be helpful for designing an adapted HPV testing and vaccination program in Tunisia.